Banana residue could be a viable rice straw alternative for Pleurotus mushroom production - Hend Hamed; Mohamed Mohamed; Khalid elshaikh; Maher Hosseney (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Oyster mushroom (Pleurotus ostreatus) is becoming more popular as an efficient biotechnological procedure for upcycling agricultural by-products into valuable human food. This study looked into the possibility of employing banana residue (BR) and sorghum stalks (SS) as localized feasible rice straw (RS) substitutes for cultivating P. ostreatus. This has the potential to improve the livelihoods of rural agricultural communities in Egypt, as well as those in other parts of the world.Method For two successive trials, three sole substrates (BR, SS, and RS) and six various combinations of SS and BR each with rice straw at 1:1, 1:2, and 2:1 ratio were tested. Agronomic features, antioxidant capacity, and crude protein contents of mushroom basidiocarps were measured.  The chemical profile of the three raw and spent sole substrates was also studied.Results The sole BR substrate was superior to both RS and SS in terms of basidiocarps yield and both exterior (average cap weight, diameter, and thickness) and interior (crude protein and total antioxidant activity, phenols and flavonoids contents) quality attributes. The yield of basidiocarps developed on the sole SS substrate was far lower than that of the other substrates. It is worth mentioning that, BR tended to contain high initial potassium, phosphorus, cellulose, and total carbohydrates concentration.Conclusion Sole BR could entirely substitute sole RS as a substrate for the production of Pleurotus ostreatus.